The socioeconomics of Ethio-Turkish relations: an appraisal of two decades - Mukerrem Miftah (Cogent Social Sciences, 2024)
Ethio-Turkish relations have gained momentum over the past few years. The first important point that demands meaningful discussion concerns the temporal genesis and contours of this momentum. The article argues that although Ethio-Turkish relations can be traced back to the sixteenth century, momentum has started to take effect since 2002. The second equally important point concerns the manner in which this momentum is expressed. By thoroughly analyzing pertinent publications and official reports, this article explains how Ethio-Turkish relations have transformed in the fields of humanitarian aid and development assistance, as well as bilateral trade and investment. However, inter alia, the study found that Turkey’s humanitarian aid and development assistance to Ethiopia do not seem to show any predictable pattern. Another critical issue worth attention is the growing challenges that have the potential to undo this momentum.